RTHP-24. TRENDS IN THE UP FRONT USE OF STEREOTACTIC RADIOSURGERY FOR GLIOBLASTOMA. (11th November 2019) - Wegner, Rodney; Abel, Stephen; Ranjan, Tulika; Williamson, Richard; Yu, Alexander; Xu, Linda; Karlovits, Stephen
Abstract: BACKGROUND: GBM is typically managed with a combined modality approach including resection followed by adjuvant chemoradiation. Despite aggressive up front treatment local failure occurs in the vast majority of patients. The concept of dose escalation through use of stereotactic radiosurgery (SRS) was tested in RTOG 9305 in the pre-temozolomide era with the hopes of improving control, ultimately showing no benefit. We used the National Cancer Database (NCDB) to examine trends in the use of up-front SRS, to see if it had truly fallen out of favor, and if it had any impact on outcome. METHODS: We queried the NCDB from 2004–14 for GBM patients that had radiation and 2 months of follow up. Odds ratios were used to determine predictors of SRS. Univariable and multivariable Cox regressions were used to determine potential predictors of overall survival (OS). Propensity adjusted multivariable analysis was used to account for any indication bias. RESULTS: We identified 62, 681 patients meeting eligibility criteria, of which 1, 046 had SRS. SRS decreased over time from 3% to less than 1%. Predictors of SRS were increased age, government insurance, lower comorbid score, treatment at an academic facility, metropolitan location, increased distance to facility, smaller tumor, lack of surgery, no chemotherapy, and more remote year of treatment. Median overall survival was 13.1 months in the non-SRS group and 12.9 months in the SRS group, p=0.28. On multivariable analysis increased age, lack of chemotherapy, higher comorbidity score, extent of surgery, non-academic facility, decreased education, government insurance, urban location, Caucasian race, male gender, larger tumor, and more remote year of treatment predicted for worse overall survival. CONCLUSIONS: Use of up-front SRS in the management of GBM has decreased over time, in concordance with past randomized trials examining its use. Our analysis did not show any benefit in survival with its use.